Molybdeunum mineralization with emphasis on porphyry systems genesis and exploration - Puig-Pichuante, R M (Rhodes University, Faculty of Science, Department of Geology, 1986)
Mo became very important in the last century, because of its sophisticated properties and its use in the new technology of alloys . Porphyry systems (porphyry Cu-Mo and Mo) contribute a significant proportion (90 - 95 per cent) to the Mo world's production. This type of deposit is associated mainly with Phanerozoic orogenic belts. Above 87per cent of the world resources are in the American Circumpacific belts , both Andean and Cordilleran . Ore grade in porphyry Cu-Mo range from 0,005 to 0,04per cent Mo, whereas in porphyry Mo grades range from 0,08 to 0,75per cent Mo . These deposits are associated with a magmatism which shows an evolution from calcic in island arcs, to calc-alkaline in magmatic back arcs, with an increase of the Mo content in the same direction. Porphyry Mo deposits display several features in common with porphyry Cu deposits. hydrothermal Similarities include nature of host alteration patterns and distribution of rock intrusives, ore minerals. An interesting difference is found in the Re contents of the molybdenite mineral. This element is higher in the molybdenites of porphyry Cu, than in those of the porphyry Mo. The ore genesis process begins involves partial melting, within enriched zones of the upper mantle and magma differentation, liquid state thermogravitational diffusion, magma convection and boiling. These processes progressively concentrate Mo in the fluids, which are released at some stage, into sulphidic hydrothermal systems, under complex geologictectonic conditions involving fracturing, brecciation and hydrothermal alteration. Major concentrations of the ore mineral are always associated with potassic alteration, and with late magmatic-early hydrothermal stages (Chilean and Western North American porphyries). Geological mapping and a close understanding of alteration and mineralization patterns, and lithogeochemistry are important tools for the exploration of porphyry Mo deposits. Geochemical prospecting, using soils, vegetation and water as sampling media, and regional aeromagnetic, gravity surveys, aerial photography and remote sensing, are us.
Keywords: Molybdenum; Porphyry